2018
DOI: 10.1371/journal.pone.0201484
|View full text |Cite
|
Sign up to set email alerts
|

The brave blue world: Facebook flow and Facebook Addiction Disorder (FAD)

Abstract: The present study investigated the relationship between flow experienced when using Facebook (Facebook flow; i.e., experience of intensive enjoyment and pleasure generated by Facebook use due to which the Facebook activity is continued even at high costs of this behavior) and Facebook Addiction Disorder (FAD). In a sample of 398 Facebook users (age: M (SD) = 33.01 (11.23), range: 18–64), the significant positive association between Facebook flow and FAD was positively moderated by the intensity of Facebook use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 35 publications
3
28
1
3
Order By: Relevance
“…More specifically, for example, reduction of interpersonal conflicts at home and at work that belong to the six main characteristics of addictive Facebook use can mainly be noticed after the clinical stay. Third, despite the positive link between duration of Facebook use and addictive Facebook use, there can be further variables that impact the level of addictive Facebook use, such as the inpatients' level of flow (see Csikszentmihalyi, 1990) experienced during the Facebook use, which was previously described to be a significant antecedent of problematic Facebook use in healthy individuals (Brailovskaia, Rohmann, Bierhoff, & Margraf, 2018). Moreover, considering that the sample consists of inpatients, it may also be that their general symptoms as well as their comorbidities affect the results.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, for example, reduction of interpersonal conflicts at home and at work that belong to the six main characteristics of addictive Facebook use can mainly be noticed after the clinical stay. Third, despite the positive link between duration of Facebook use and addictive Facebook use, there can be further variables that impact the level of addictive Facebook use, such as the inpatients' level of flow (see Csikszentmihalyi, 1990) experienced during the Facebook use, which was previously described to be a significant antecedent of problematic Facebook use in healthy individuals (Brailovskaia, Rohmann, Bierhoff, & Margraf, 2018). Moreover, considering that the sample consists of inpatients, it may also be that their general symptoms as well as their comorbidities affect the results.…”
Section: Discussionmentioning
confidence: 99%
“…Flow is defined as a “state in which people are so involved in an activity that nothing else seems to matter; the experience is so enjoyable that people will continue to do it even at great cost, for the sheer sake of doing it” ([ 47 ]; page 4). However, flow experienced during Facebook use was reported to be an antecedent of addictive tendencies [ 48 , 49 ]. The positive feelings that are linked to the flow experience often contribute to further immersion into the online world, and may cause the development of a close emotional bond to the SNS [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the literature, it would appear that both attentional and emotional processes could be contributors in the emergence of compromised time control among gamers. It has been repeatedly shown that having fun and enjoying an activity helps individuals experiencing a flow state (e.g., Brailovskaia et al 2018;Corcos 2018;Limperos et al 2011). Therefore, it could be hypothesized that since disordered gamers react more strongly to gaming stimuli, and can associate negative outcomes with pleasure, not only will it be easier for them to underestimate time, but they will also tend to experience flow states more easily than healthy gamers (e.g., Ko et al 2013;Ravaja et al 2006).…”
Section: Discussionmentioning
confidence: 99%